THE RELEVANCE OF KH AHMAD DAHLAN'S EDUCATION MODEL IN THE ERA OF SOCIETY 5.0 - Euis Asyiah; Eneng Muslihah; Shobri (Kaffah: Jurnal Pendidikan dan Sosio Keagamaan, 2024)
This study explores and discovers the relevance of the educational model introduced by KH Ahmad Dahlan in facing the Era of Society 5.0. The research method used is qualitative research with a literature analysis approach to understand the educational principles adopted by KH. Ahmad Dahlan. The results showed that the values of Islamic education instilled by KH Ahmad Dahlan such as honesty, justice, and integrity as well as social care have significant relevance in the Era of Society 5.0. Through a qualitative approach, it was found that the leadership model can positively contribute to the development of the character and competence of the younger generation in facing the challenges of digital transformation. Researchers found that the education taught by KH Ahmad Dahlan is inclusive education where all children from various groups have the right to education. The leadership model of Dr. KH Ahmad Dahlan is a prophetic leadership model in establishing the Muhammadiyah organization.